Volatile characterization of crude and refined walnut oils from aqueous enzymatic extraction by GC-IMS and GC-MS - Jiankang Deng; Huibo Zhao; Bing Qi; Di Wang; Yanbing Wu; Shengxing Dai; Junxia Xia; Min Lu; Kuizhang Yao; Aijin Ma; Yingmin Jia (Arabian Journal of Chemistry, 2024)
The aroma characteristics of crude walnut oil (CWO) and soft-refined walnut oil (RWO) were analyzed using gas chromatography-ion mobility spectrometry (GC-IMS) and headspace gas chromatography-mass spectrometry (HS-SPME-GC-MS). CWO was obtained from walnut samples of seven varieties in Yunnan using aqueous enzymatic extraction (AEE), while RWO was produced by deacidifying and dehydrating CWO. Comprehensive analyses using both GC-IMS and HS-SPME-GC-MS were performed to discern the volatile compounds in CWO and RWO. Chemometric techniques including hierarchical clustering analysis (HCA), principal component analysis (PCA), stepwise linear discriminant analysis (PLS-DA), and orthogonal partial least square discriminant analysis (OPLS-DA) were employed for the characterization and classification of the oils. The results indicated that GC-IMS served as an excellent complementary technique to GC-MS for aroma characterization. Additionally, PLS-DA was found to be effective for categorizing walnut oil based on HS-GC-IMS. Through GC-MS and OPLS-DA, a clear distinction between CWO and RWO samples was established. The outcomes indicated that both CWO and RWO contained distinct volatile compounds, and the refining process impacted the composition of volatile compounds in the oils. This research sheds light on the volatile substances in walnut oils and their changes during the refining process, enhancing insights into moderate processing of walnut oil.